2006
DOI: 10.1530/rep.1.00933
|View full text |Cite
|
Sign up to set email alerts
|

Regulated expression of two sets of paternally imprinted genes is necessary for mouse parthenogenetic development to term

Abstract: Mouse parthenogenetic embryos (PEs) are developmentally arrested until embryo day (E) 9.5 because of genomic imprinting. However, we have shown that embryos containing genomes from non-growing (ng) and fully grown (fg) oocytes, i.e. ng wt /fg wt PE (wt, wild type), developed to E13.5. Moreover, parthenogenetic development could be extended to term by further regulation of Igf2 and H19 expression using mice with deletion of the H19 transcription unit (H19D13) together with its differentially unit (DMR). To gain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…Kono and co-workers showed that a 13 kb deletion encompassing the H19 coding region and the upstream differentially methylated region (DMR) allows parthenogenetic embryos to develop to term [22]. The efficiency of full-term development significantly increases when the H19/Igf2 DMR together with the DMR found within a second imprinted gene cluster Dlk1/Dio3 on chromosome 12 are deleted [23,32]. Most recently Hikichi et al showed that the development of PG embryos can be extended following serial nuclear transfer (NT) and is associated with a decrease in H19 expression [33].…”
mentioning
confidence: 99%
“…Kono and co-workers showed that a 13 kb deletion encompassing the H19 coding region and the upstream differentially methylated region (DMR) allows parthenogenetic embryos to develop to term [22]. The efficiency of full-term development significantly increases when the H19/Igf2 DMR together with the DMR found within a second imprinted gene cluster Dlk1/Dio3 on chromosome 12 are deleted [23,32]. Most recently Hikichi et al showed that the development of PG embryos can be extended following serial nuclear transfer (NT) and is associated with a decrease in H19 expression [33].…”
mentioning
confidence: 99%
“…We carried out further methylation analysis of the IG-DMR of Dlk1-Gtl2 in survivor ng Δch7 /fg BMEs. Interestingly, we observed a higher frequency of hypermethylated patterns in the ng Δch7 allele and partial methylation in the fg allele [21]. The reason for the different IG-DMR methylation patterns of Dlk1 in the ng Δch7 /fg BMEs is unknown.…”
Section: Riddle Arising From Birth Of "Kaguya"mentioning
confidence: 70%
“…Fetal development is promoted generally by paternally expressed genes (Wu et al, 2006), whereas maternally expressed genes have a tendency to restrict fetal growth (Abu-Amero et al, 2008). Imprinting is found predominantly in placental mammals, and may participate in the balance of parental resource allocation to the offspring (Ishida and Moore, 2013).…”
Section: Introductionmentioning
confidence: 99%